Avaliação da retinopatia diabética em pacientes com diabetes mellitus tipo 1 no Hospital universitário–UFMA - PAIVA, Fernando Cleydson Lima (2019)
Introduction: Diabetic retinopathy (DR) is classically considered a vascular disease, current evidence establishes neurodegenerative processes as an important factor in the etiopatology of this disease. Aiming at the early detection of neurodegenerative changes in patients with type 1 diabetes mellitus without DR or in their early stages, spectral domain optical coherence tomography (SD-OCT) was performed for structural retinal analysis in these patients. Methods: Patients with type 1 diabetes mellitus (DM1) were evaluated and complete ophthalmologic examination and laboratory tests were performed. Retinographic examinations were performed and analyzed by two independent examiners for concordance analysis of intra-and inter-examiner staging. SD-OCT tests were performed to verify the thickness and volume of the macular area, the thickness of the ganglion cell layer/ internal plexiform layer (GCL / IPL) and the mean thickness of the retinal nerve fiber layer (RNFL), observing the normality data provided by the device's own algorithms to evaluate early neural retinal involvement. Results: Of a total of 98 patients, after exclusion criteria, 158 eyes were analyzed from 79 patients with DM1, 53.2% were males with mean age of 30.1 ± 9.6 years and mean DM1 time 14.2 ± 8 years. The majority of the patients presented absence of DR (53.8%) or mild DR(16.5%). The agreement of the results of the intraclassse retinographic examinations was excellent (coefficients = 0.879 and 0.758, for examiners 1 and 2, respectively; P <0.001) and there was good concordance among examiners (coefficient = 0.692; P <0.001). The DR stage had a direct correlation with DM time. Regarding the results of the SD-OCT tests, a decrease in the measured and minimal thickness of the GCL / IPL complex related to the increase of DM1 time was observed. Regarding the results of SD-OCT tests, a decrease in the minimum thickness of the GCL / IPL complex was observed in patients with DR compared to patients without DR. Conclusion: Neurodegenerative changes of the internal retina may precede the vascular alterations in patients with DM1 and may be the earliest criterion of DR.